Cli-fi Young Adult et imaginaire urbain : (re)configurations génériques - Natacha Levet (ReS Futurae)
Young Adult Cli‑Fi benefits from young readers appetite for science fiction and dystopia and the attention they give to environment, climate crisis and ecology. These novels often relay media cliché about some kind of fiction talking about present time or near future (Langlet, 2020). Furthermore, young adult cli-fi continues historic tension between entertainment and knowledge literature for young readers. On one hand, entertainment with no real concern for scientific plausibility, on the other hand, commitment to raise consciousness and motivate action, with scientific basis. This paper will study through French novels the reconfiguration of cities in young adult cli-fi, between cultural and generational conventions and ecofictional requirement (Chelebourg, 2012).Cultural and generational references feed urban imaginations. Scientific basis, fundamental in cli‑fi, adapt to the needs of educational purpose. Urban spaces are plausible regarding our present and knowledge, far from the sci‑fi estrangement experience.These novels are cli-fi but also teen novels. Urban spaces express disaster imagination but may be some ground for game and initiation. Through this symbol of adult hubris, the opposition between kids and adults renews, according to the dystopian model (Bazin, 2019). Young and ecofictional heroes may have different purposes: save the world, giving grandeur back to humanity, or leave the City to create a new society, with ou without cities.